SIMULATION-BASED LEARNING TECHNOLOGIES IN PHYSICAL THERAPY FOR DEVELOPING PROFESSIONAL COMPETENCIES OF MASTER’S STUDENTS IN SPECIALTY 227 “THERAPY AND REHABILITATION” - Bilous, O. S.; Kalashchenko, S. I.; Hrynzovskyi, A. M. (Rehabilitation and Recreation, 2025)
The article evaluates the effectiveness of traditional and modern educational technologies in teaching the discipline «Simulation-Based Learning Technologies in Physical Therapy» for Master's students of specialty 227 «Therapy and Rehabilitation» at Bogomolets National Medical University (hereinafter – Bogomolets NMU). It also analyzes the advantages and disadvantages of the implemented teaching methods in order to improve the quality of the educational process. The purpose of the study is to determine the effectiveness of the applied teaching methods, particularly simulation technologies, in the education of future professionals in the field of physical therapy. Material. An anonymous online survey was conducted using Google Forms, which included five sections of questions: respondent data, evaluation of the course content, evaluation of teaching methods, assessment of simulation-based learning, impressions, and suggestions. The survey was completed by a group of Master's students (n=16) who studied the discipline «Simulation-Based Learning Technologies in Physical Therapy» for the first time at the Department of Emergency and Tactical Medicine of Bogomolets NMU. Results. According to the survey results, 93.8% of students highly rated the use of simulation technologies, such as virtual reality and standardized patients, for practicing clinical skills. Students also noted the effectiveness of the Case-Based Learning (CBL) method in developing their clinical reasoning, as well as the benefits of interactive VR simulations and analysis of real clinical cases. Based on the findings, most respondents indicated that these methods contribute to a better understanding of the learning material and increased self-confidence. Conclusions. The results of the study indicate that the course «Simulation-Based Learning Technologies in Physical Therapy» for Master's students at Bogomolets NMU received a positive response from students. Most respondents highly appreciated the effectiveness of integrating modern technologies into the educational process, confirming their interest in the further application of such methods in their professional activities. However, some students pointed out the need for deeper integration of interactive VR simulations into the structure of practical classes to better consolidate acquired knowledge.